2014
DOI: 10.1007/s10590-014-9153-0
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid machine translation architecture guided by syntax

Abstract: This article presents a hybrid architecture which combines rule-based machine translation (RBMT) with phrase-based statistical machine translation (SMT). The hybrid translation system is guided by the rule-based engine. Before the transfer step, a varied set of partial candidate translations is calculated with the SMT system and used to enrich the tree-based representation with more translation alternatives. The final translation is constructed by choosing the most probable combination among the available frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Despite the inability of the two metrics to establish a specific level of quality, we have compared the scores with those reported in other experiments for Basque (Díaz de Ilarraza et al 2008, España-Bonet et al 2011, Labaka et al 2014, 2016 and confirmed that they are in the same range. Given the impact MT quality has on post-editing opportunities, we hoped to provide workshop participants with MT quality similar to that attainable by state-of-the-art generic systems for the Spanish-Basque language direction such as that reported in Labaka et al (2014).…”
Section: The Machine Translation Systemssupporting
confidence: 52%
See 1 more Smart Citation
“…Despite the inability of the two metrics to establish a specific level of quality, we have compared the scores with those reported in other experiments for Basque (Díaz de Ilarraza et al 2008, España-Bonet et al 2011, Labaka et al 2014, 2016 and confirmed that they are in the same range. Given the impact MT quality has on post-editing opportunities, we hoped to provide workshop participants with MT quality similar to that attainable by state-of-the-art generic systems for the Spanish-Basque language direction such as that reported in Labaka et al (2014).…”
Section: The Machine Translation Systemssupporting
confidence: 52%
“…Given the impact MT quality has on post-editing opportunities, we hoped to provide workshop participants with MT quality similar to that attainable by state-of-the-art generic systems for the Spanish-Basque language direction such as that reported in Labaka et al (2014). In terms of system differences, we observed that in week 6, when Google Translate was used, scores were substantially lower, confirming the experience of the IXA research group and the perception of workshop participants, who complained about the decrease in quality after completing the tasks for week 6.…”
Section: The Machine Translation Systemsmentioning
confidence: 99%
“…Also rule-based systems can be enhanced with statistical components (Habash and Monz 2009). It is claimed that better translation results can be achieved using a hybrid combination of these approaches (Labaka et al 2014). Nevertheless, the quality of translation continues to be relatively low and research continues for finding better quality testing methods (Felice and Specia 2013;Birch et al 2010).…”
Section: Hybrid Approachmentioning
confidence: 99%
“…Apart from the WMT shared task translation systems [18] presented a hybrid machine translation architecture guided by syntax. In this work, the authors develop a hybrid translation system guided by the rule based machine translation engine and, before transference, few partial candidate translations given by the statistical translation schemes.…”
Section: Previous Workmentioning
confidence: 99%